The Role of Thinking Across in the Concept of Dynamic Governance in Educational Services - Widya Kurniati Mohi; Muh. Firyal Akbar (Journal La Edusci, 2025)
This study examines the role of Thinking Across within the Dynamic Governance framework in the governance of educational services at Private Higher Education Institutions in Gorontalo Province. It aims to explore how Thinking Across, which includes cross boundary leadership, interdisciplinary collaboration, and cross sector integration, is internalized and operationalized in institutional practices. This study employed a qualitative multiple case study approach involving five private universities. Data were collected through in depth interviews, observations, and document analysis, and were analyzed thematically to identify patterns of governance practices and institutional dynamics. The findings show that the implementation of Thinking Across remains partial and uneven across institutions. Although awareness of the importance of collaboration across institutional and disciplinary boundaries has grown, its translation into consistent governance practices is still limited. Interdisciplinary initiatives and cross sector collaborations have begun to emerge through selected academic programs, collaborative research, and partnerships with external stakeholders. However, these efforts remain fragmented and are often driven by individual initiative rather than institutionalized mechanisms. The study also identifies several major challenges, including limited institutional capacity, weak coordination across units, regulatory rigidity, and insufficient digital integration for data driven decision making. These findings underscore the importance of strengthening institutional structures, fostering a collaborative culture, and improving digital integration to support adaptive governance. The study contributes to Dynamic Governance literature by highlighting the significance of cross disciplinary and cross sector integration in the transformation of higher education governance, particularly in resource constrained regional institutions.